2006
DOI: 10.1029/2006wr005031
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic reactive diffusion of uranium in the contaminated sediments at Hanford, United States

Abstract: [1] Microscopic and spectroscopic analyses of uranium-contaminated sediments from select locations at the U.S. Department of Energy (DOE) Hanford site have revealed that sorbed uranium (U) often exists as uranyl precipitates associated with intragrain fractures of granitic clasts. The release of U to contacting fluids appears to be controlled by intragrain ion diffusion coupled with the dissolution kinetics of the precipitates that exist in the form of Na-boltwoodite. Here we present a coupled microscopic reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 33 publications
3
85
1
Order By: Relevance
“…These sediments are physically and mineralogically heterogeneous and could contain microsites where advection forces are low (29) and hot spots (33) where electron donors are relatively concentrated. This circumstance would generate microenvironments of O 2 depletion where anaerobic respiration could occur.…”
Section: Discussionmentioning
confidence: 99%
“…These sediments are physically and mineralogically heterogeneous and could contain microsites where advection forces are low (29) and hot spots (33) where electron donors are relatively concentrated. This circumstance would generate microenvironments of O 2 depletion where anaerobic respiration could occur.…”
Section: Discussionmentioning
confidence: 99%
“…White and Brantley [2003], Maher et al [2006]). In contrast to the 1-D study of Liu et al[2006], 2-D pore scale modeling efforts , ) found that spatial distributions of reactivity under advective conditions can lead to different observed macroscopic rate behavior even though the total reactivity between simulations was the same. In column experiments pore scale water velocities caused by particle scale heterogeneities have been linked with observed reaction rates ), although the cause of this link has yet to be delineated (Zhang et al [2008], Chen and Wagenet [1995], which also include data at: 1) batch to column scales, 2) bench (batch or column scales)…”
Section: Physical Controls On Metal/radionuclide Behaviormentioning
confidence: 81%
“…In Liu et al [2006] a combined experimental and modeling study was completed to explore chemical reactivity and intragranular diffusion. Through extensive characterization of micro-scale chemical heterogeneities (Liu et al [2004]) a conceptual model was created to explain the slow release of uranium from micro-precipitates present in fractures deep within the porous media.…”
Section: Physical Controls On Metal/radionuclide Behaviormentioning
confidence: 99%
“…At shallower depths, EXAFS analyses suggest that the major uranium-controlling phase was meta-torbernite, Cu(UO 2 ) 2 (PO 4 ) 2 ā€¢ xH 2 O (Catalano et al 2006b;Arai et al 2007) with uranyl-carbonate precipitates, predominantly consistent with uranium-rich calcite (Catalano, personal communication). Until recently, it had been speculated that the uranyl-silicate phase present in the 300 Area sediments was either Na-boltwoodite, Na(UO 2 )(SiO 3 OH) ā€¢ xH 2 O, or uranophane, Ca(UO 2 ) 2 [SiO 3 (OH)] 2 ā€¢ xH 2 O-both minerals have the uranophane group structure (Liu et al 2004;Liu et al 2006;Zachara et al 2005;McKinley et al 2006;McKinley et al 2007). The minute inclusions, which prevent bulk analyses, and similarities between the uranophane group structures had precluded conclusive identification of the uranyl-silicate phase.…”
Section: 7mentioning
confidence: 99%